(untitled) (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2026)
This paper focuses on analyzing the authentic meaning of khalīfah as stipulated in the Qur’an. Using a descriptive-exploratory qualitative method, this paper reveals the original meaning of khalīfah from three perspectives of tafsīr riwāyah, dirāyah, and isyārah and correlates it with the role of Islamic educational institutions, particularly in relation to science education. Investigating the original meaning of khalīfah is critical for at least three reasons: (a) the meaning of khalīfah or khilāfah has been distorted into merely political power; (b) Islamic education pays insufficient attention to the study of secular subjects in general; and (c) secular subjects, including science, are widely perceived as less important than so-called religious studies. An in-depth study of the notion of khalīfah suggests the opposite: knowledge of the universe and material things commonly deemed secular is in fact the very factor that makes human beings exceptional, even more glorious than the angels, and justifies why Adam was chosen as khalīfah. Secular subjects therefore carry the same spiritual weight as religious ones, if not more. The paper further argues that this reconceptualization has direct implications for curriculum policy and pedagogy in Islamic educational institutions, providing a stronger theological rationale for treating science education as an integral part of Islamic learning rather than a peripheral, secular add-on.